Immune responses of leishmaniasis patients to heat shock proteins of Leishmania species and humans. - Skeiky, Y A (1995)
The course of human infection with Leishmania braziliensis is variable, ranging from self-healing infection to chronic disease. It is therefore a useful system in which to study immunoregulatory aspects of leishmaniasis, including the effects of parasite antigens on host responses. In the present study, we report on the cloning of, expression of, and comparative analyses of patient immune response to two different L. braziliensis genes homologous to the genes for the eukaryotic 83- and 70-kDa heat shock proteins. rLbhsp83 contains a potent T-cell epitope(s) which stimulated peripheral blood mononuclear cells (PBMC) from all L. braziliensis-infected individuals to proliferate and to produce interleukin-2 (IL-2) gamma interferon, and tumor necrosis factor alpha. The elicitation of IL-4 and IL-10 mRNAs was found to differ depending on the portion of the rLbhsp83 used to stimulate PBMC. rLbhsp83a, which represents the nearly full-length protein, stimulated IL-10 but not IL-4 mRNA. In contrast, a approximately 43-kDa protein representing the C-terminal region of Lbhsp83 stimulated the production of IL-4 but not IL-10 mRNA. rLbhsp70 stimulated PBMC proliferation from patients with mucosal disease but, unlike rLbhsp83, did not stimulate PBMC from self-healing individuals. PBMC from mucosal patients were not stimulated by rHuhsp70 to either proliferate or produce cytokines. This suggests that the hyperresponsiveness of mucosal patient PBMC to Leishmania heat shock proteins does not involve an auto-immune phenomenon resulting from cross-reactivity with self hsp70. In general, although the cytokine profile of patient PBMC in response to both of these Leishmania heat shock proteins represents a mixed Th1-Th2 pattern, the levels of gamma interferon and IL-2 were significantly higher than those of the Th2 cytokines IL-4 and IL-10. Patients with active mucosal and cutaneous disease but not self-healing individuals had significant anti-immunoglobulin G antibody titers to both rLbhsp83 and rLbhsp70 but not to the homologous rHuhsp70. It therefore appears that differential patient immune responses to Leishmania hsp83 and hsp70 may be of particular significance in the induction of protective immune responses as well as in the development of tissue damage in cases with particularly strong hypersensitive reactions.